Climate Change Effects on Grapevine Physiology and Biochemistry: Benefits and Challenges of High Altitude as an Adaptation Strategy - Arias, Leonardo A.; Berli, Federico; Fontana, Ariel; Bottini, Rubén; Piccoli, Patricia (Frontiers in Plant Science, 2022)
Grapevine berry quality for winemaking depends on complex and dynamic relationships between the plant and the environment. Winemakers around the world are demanding a better understanding of the factors that influence berry growth and development. In the last decades, an increment in air temperature, CO2 concentration and dryness occurred in wine-producing regions, affecting the physiology and the biochemistry of grapevines, and by consequence the berry quality. The scientific community mostly agrees in a further raise as a result of climate change during the rest of the century. As a consequence, areas most suitable for viticulture are likely to shift into higher altitudes where mean temperatures are suitable for grape cultivation. High altitude can be defined as the minimum altitude at which the grapevine growth and development are differentially affected. At these high altitudes, the environments are characterized by high thermal amplitudes and great solar radiations, especially ultraviolet-B (UV-B). This review summarizes the environmental contribution of global high altitude-related climatic variables to the grapevine physiology and wine composition, for a better evaluation of the possible establishment of vineyards at high altitude in climate change scenarios.